Insular insight where art and architecture conspire with nature : Naoshima, Teshima, Inujima - Müller, Lars 1955-; Miki,Akiko; Kagayama, Hiroshi ([Baden, Switzerland] Lars Müller Publishers Fukutake Foundation, 2011)
The islands of Naoshima, Teshima, and Inujima in Japan’s Seto Inland Sea are places of pilgrimage for friends of contemporary art and architecture. Alongside works in public spaces as well as site-specific installations, the islands are also full of numerous museums and collections of contemporary art. This publication offers a comprehensive documentation of this unique cultural landscape surrounded by Japan’s Inland Sea. The photographs by the Dutch photographer Iwan Baan, ranging from tiny details to giant panoramas, create a comprehensive portrait of the islands with their fluid transitions between nature, art, and architecture. Numerous texts introduce readers to the individual areas and projects that are either permanently on display on the islands or have taken place there temporarily. In addition, other essays deal with the island as a cultural concept and phenomenon. Among others, the book presents buildings by Kazuyo Sejima, Ruye Nishizawa, Tadao Ando, and Hiroshi Sambuichi.--Provided by publisher.
Includes bibliographical references.
Keywords: Fukutake, Soichiro -- 1945-.; Baan, Iwan -- 1975-; Art museums -- Japan -- Inland Sea Region; Architecture -- Japan -- Inland Sea Region; Art -- Japan -- Inland Sea Region; Art, Modern -- 20th century; Art, Modern -- 21st century; Architecture -- 21st century. -- Japan -- Naoshima-chō.; Architecture -- Japan -- Naoshima-chō.; Resort architecture -- Japan -- Naoshima-chō.; Architects -- Japan; Inland Sea Region (Japan) -- Description and travel; Naoshima-chō (Japan) -- Buxldings, structures, etc